(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
This article discusses one of the most urgent problems of modern education system in South Korea – the problem of shadow education. Analyzes the main forms of shadow education, negative and positive aspects are considered measures of political influence on the he normalization of the situation in the informal education.